2020
DOI: 10.1002/cite.202000043
|View full text |Cite
|
Sign up to set email alerts
|

Digital Extraction Column: Measurement and Modeling Techniques

Abstract: The digitization of extraction columns requires a profound knowledge of the present hydrodynamics/mass transport interaction as well as appropriate measurement techniques for the detection of relevant input and target values. In this article, the different techniques for droplet size distribution as well as concentration determination are presented and new methods for online evaluation are discussed. In combination with the simulation of droplet size, holdup and solute concentration distribution, an online-cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 60 publications
0
5
0
1
Order By: Relevance
“…In the last few decades, image postprocessing techniques to extract the features of drops have been successfully developed. , For a single drop, the subduction method was used for drop identification, that is, to distinguish the profile of the drop by subtracting the sequenced image from a reference image. Then, the drop was presented as a white dot by the application of threshold and binarization.…”
Section: Measuring Techniquesmentioning
confidence: 99%
“…In the last few decades, image postprocessing techniques to extract the features of drops have been successfully developed. , For a single drop, the subduction method was used for drop identification, that is, to distinguish the profile of the drop by subtracting the sequenced image from a reference image. Then, the drop was presented as a white dot by the application of threshold and binarization.…”
Section: Measuring Techniquesmentioning
confidence: 99%
“…The development of this type of ''smart equipment'' by using new sensor or ML solutions to determine hard-to-measure variables and offer more process flexibility has attracted considerable attention in academic and industrial research [1,4,26]. Some examples include the digitalization of extraction columns by means of novel measurement techniques complemented by modeling and simulation methods to create tools for predictive online monitoring, which is reviewed in Hlawitschka et al [27]. Other approaches work on the integration of novel sensors and actuators to obtain valuable process information and create more responsive equipment [28].…”
Section: Kernel Density Estimation Decision Treementioning
confidence: 99%
“…Some examples include the digitalization of extraction columns by means of novel measurement techniques complemented by modeling and simulation methods to create tools for predictive online monitoring, which is reviewed in Hlawitschka et al 27. Other approaches work on the integration of novel sensors and actuators to obtain valuable process information and create more responsive equipment 28.…”
Section: Introductionmentioning
confidence: 99%
“…In these studies, terms of drop behaviors usually come from two ways: from the previous literature or from the single drop study 25 . PBM based on the single drop study was found promising in scale‐up design of the column 26 and has a potential to reduce pilot test requirements 27 . However, one of the challenges is to obtain a set of robust parameters, 28 as they are always limited to a certain column geometry and specific test systems.…”
Section: Introductionmentioning
confidence: 99%